Analisis Keterkaitan Antar Sektor dan Identifikasi Sektor Unggulan dalam Perekonomian Provinsi Sumatera Barat Menggunakan Pendekatan Input-Output - I Wayan Suparta; Chelilla Khalisya Putri; Zahra Syifa Fauziah; Riris Tamaria Simbolon; Naila Salsabila; Nanda Meilania Bardes; Helena Sherin Salsabie (Journal of Innovative and Creativity (Joecy), 2026)
This study analyzes the inter-sectoral linkages and identifies leading sectors in the economy of West Sumatra Province using the Input-Output approach. The three main sectors analyzed are agriculture, manufacturing industry, and construction. Based on the technical coefficient matrix and Leontief inverse, agriculture has the highest backward linkage value of 1.142, followed by construction (0.916) and manufacturing (0.942). In terms of multiplier effects, agriculture also records the highest output multiplier of 1.269 and income multiplier of 0.462. These results indicate that the agricultural sector plays the most strategic role in driving economic activity in West Sumatra, both in terms of inter-sectoral linkages and multiplier effects on output and income. These findings have implications for regional development policy, where investment and development prioritization in the agricultural sector is expected to provide broader economic impacts.